PENGARUH TEKNOLOGI INFORMASI TERHADAP KECERDASAN (INTELEKTUAL, SPIRITUAL, EMOSIONAL DAN SOSIAL) STUDI KASUS: ANAK-ANAK - Gilang Wisnu Saputra; Muhammad Aldy Rivai; Mawaddatus Su’udah; Shepty Lana Gust Wulandari; Tyas Rosiana Dewi; Fitroh Fitroh (UIN Syarif Hidayatullah Jakarta, 2017)
The use of information technology (IT) has a positive impact and negative depending on the user's ability to use it, not to mention children. Discretion in the use of IT has considerable influence for the formation of a child's brain ability and will affect the level of intelligence of children. Parents have a role to be aware of changes that occur during the growth of the child. This study will show how far the changes that occur in children after they use information technology and what impact information technology that has a positive effect or a negative for the level of intelligence of children consisting of intellectual, emotional, spiritual, and social terms of parents. This research uses descriptive quantitative method by using questionnaire data collection, data processing, data analysis and interpretation of data. The results showed that information technology has a considerable impact both on four areas of intelligence of children who have been mentioned by values obtained from the calculation of the questionnaires. The results of the questionnaires calculation for intellectual acumen have an adverse impact, influence of IT on emotional intelligence has a pretty good impact, influence IT has an influence on spiritual intelligence is quite good, and the influence of IT for social intelligence has a good impact on the level of social intelligence of children child.